Placental abruption as a trigger of DIC in women with HELLP syndrome: a population-based study. (2nd September 2022) - Gomez-Tolub, Rachel; Rabinovich, Anat; Kachko, Eric; Benshalom-Tirosh, Neta; Tirosh, Dan; Thachil, Jecko; Besser, Limor; Than, Nandor Gabor; Erez, Offer
Abstract: Background: Disseminated Intravascular Coagulation (DIC) is a life-threatening condition. Hemolysis, Elevated Liver enzymes and Low Platelets (HELLP) syndrome is one of the obstetrical syndromes mostly associated with DIC and thus, high rates of fatal complications. There is a lack of information regarding epidemiologic and clinical characteristics of women who developed HELLP syndrome with and without DIC. Additionally, until now, there is no adapted and widely accepted way to diagnose DIC among pregnant women presenting with HELLP syndrome, despite the evident maternal mortality linked to the disease. Objectives: ( 1) Address the gaps in knowledge regarding the prevalence, epidemiologic and clinical characteristics of women with HELLP syndrome who develop DIC; and (2) determine the risk factors for the development of DIC among women with HELLP syndrome. Study design: This was a population-based retrospective cohort study, including all women who delivered at the Soroka University Medical Center between the years 2001–2017. The study population was divided into three groups: (1) comparison group ( n = 207, 266 deliveries); (2) HELLP syndrome without DIC ( n = 320); (3) HELLP syndrome with DIC ( n = 21). The diagnosis of DIC was based on the ICD-9 code as recorded in the obstetrical database of the Soroka University Medical Center. The coding is based on the diagnosis made by the attending physician during hospitalization. Results: (1) The rate of HELLP syndrome in the study population was 0.16% (341/207, 607), of them 6.16% (21/341) had DIC; (2) among patients with HELLP syndrome, those with DIC had a higher median gravidity and parity; (3) a higher rate of severe maternal morbidity including blood product transfusion, placental abruption, eclampsia, acute renal failure and maternal death was observed in those who had HELLP syndrome and DIC compared to those with HELLP syndrome without DIC and the comparison group ( p -value <.001 for comparison among the three groups); (4) among women with HELLP syndrome, those with DIC had a longer median PT difference, higher serum creatinine and lower AST as well as ALT median concentrations than those without DIC; (5) patients with HELLP syndrome and DIC had a higher rate of stillbirth and postpartum death than patients in the other groups ( p -value <.001 for comparison among the three groups); and (6) placental abruption was an independent risk factor for the development of DIC in women with HELLP syndrome ( p -value <.001). Conclusions: (1) Among women with HELLP syndrome, those who developed DIC had a higher rate of maternal and neonatal morbidity and mortality than those without DIC; and (2) placental abruption, but not abnormal liver function, was an independent risk factor for the development of DIC in women with HELLP syndrome.